SOCIAL NETS AS A NEW FACTOR OF SYSTEM SECURITY IN RUSSIA IN THE 21ST CENTURY - S. A. Kravchenko; A. I. Podberezkin (Vestnik MGIMO-Universiteta)
The article analyzes the interconnection of social aspects of the Internet and security issues in Russia. It shows that contemporary realities acquire global network character that has ambivalent impact on the development of civilizational and social interactions. On the one hand, social networks offer new opportunities for interaction between people living in different countries, on the other hand - they can be used for exclusion at the global level which objectively produces new risks and vulnerabilities. Special consideration is given to fabrication of global risk in social networks, which may provoke military-political conflicts and even wars. In the context of growing pragmatism and globalization of activities of agents of Western civilization the networks take on the quality of the new and highly effective weapon intended to destroy and destroy high-priority policy objectives. The authors analyze the nature of contemporary politics and the war from the perspective of social networks as policy and war tools. Overcoming new security risks and vulnerabilities authors see in the ways of changing the vector of development of scientific knowledge from a pragmatic to a humanist mode.